Organophosphate Poisoning in a Paediatric Intensive Care Unit: A Retrospective Analysis Based on Ten Years of Experience - Yousef A; Albuali W; AlOmari M; AlMutairi A; Albuali HW; AlQurashi FO; Alshaqaq HM (International Journal of General Medicine, 2022)
Abdullah Yousef,1 Waleed Albuali,1 Mohammed AlOmari,1 Abdullah AlMutairi,1 Hamad W Albuali,2 Faisal O AlQurashi,1 Hassan M Alshaqaq2 1Department of Pediatrics, College of Medicine, Imam Abdulrahman Bin Faisal University, Dammam, Saudi Arabia; 2College of Medicine, Imam Abdulrahman Bin Faisal University, Dammam, Saudi ArabiaCorrespondence: Waleed Albuali, Department of Pediatrics, College of Medicine, Imam Abdulrahman Bin Faisal University, Dammam, Saudi Arabia, Tel +96638966877 ext. 1616, 1226, Email wbuali@iau.edu.sa; wbuali0000@gmail.comBackground: Organophosphate (OP) poisoning is one of the most common etiologies of poisoning in the pediatric age group.Objective: This study aimed to evaluate the demographic characteristics, clinical features, clinical course, and outcomes of children with toxicity from organophosphates admitted to the pediatric intensive care unit.Methods: A retrospective review of hospital medical records of all children aged 14 years and younger who were admitted to the PICU with a provisional diagnosis of organophosphate poisoning at King Fahad Hospital of the University (KFHU), Alkhobar, Saudi Arabia, between January 1, 2008, and December 31, 2018, was conducted. Patients with incomplete medical record information or with suspicion or evidence of one or more agents other than organophosphate were excluded from the study.Results: Thirty-one patients were enrolled in the study. The median age of the study population was 2 years, and 19 (61%) were males. The majority of patients (68%) had more than one route of organophosphate exposure. Skin exposure was reported in 26 patients (84%). Only three patients (10%) had suicidal organophosphate exposure from organophosphates, while the majority (28 patients; 90%) had accidental poisoning. Bronchorrhea was the most prevalent presenting feature, reported in 28 patients (90%). 17 patients (55%) were treated with intravenous atropine and (45%) were used a combination of pralidoxime with atropine for treatment. Five patients (16%) developed acute respiratory distress syndrome. Twelve patients (39%) needed endotracheal intubation and mechanical ventilation secondary to respiratory failure.Conclusion: The presenting features of organophosphate poisoning differ widely in children. Risk factors for mortality for PICU patients with organophosphate poisoning include delayed hospital arrival by more than 1 hour, inhalational route of exposure, need for mechanical ventilation, and high lactate levels in the first 24 hours post-exposure.Keywords: organophosphate, poisoning, toxicology, pediatric, intensive care